Evaluasi Keterpakaian Koleksi Terhadap Minat Kunjung Siswa-Siswi di Perpustakaan Madrasah Aliyah Negeri 1 Padang Lawas - Dinda Rizki Anggurini Hasibuan; Laila Rohani; Yusniah (IAI Nasional Laa Roiba Bogor, 2025)
This study aims to determine the impact of library collection usability on students' interest in visiting the library at Madrasah Aliyah Negeri 1 Padang Lawas. The research employed a quantitative methodology with an associative approach to analyze the relationship between the variables of collection usability (X) and students' interest in visiting the library (Y). Data were collected through surveys and analyzed using statistical techniques, including Product Moment correlation analysis and simple linear regression with the help of SPSS version 22. The results indicated a positive and significant relationship between collection usability and students' interest in visiting the library, with a correlation coefficient of 0.373. Hypothesis testing showed that library collection usability positively and significantly affects students' interest in visiting the library, accounting for 45.9% of the variance explained by the collection usability variable. These findings emphasize the importance of improving the quality and relevance of library collections to enhance students' interest in visiting the library